1975
DOI: 10.1084/jem.142.6.1455
|View full text |Cite
|
Sign up to set email alerts
|

Dominant nonresponsiveness in the induction of autoimmunity to liver-specific F antigen.

Abstract: The liver-specific F antigen, although not an autoimmunogen, can induce the production of autoantibodies in responder strains. The ability to respond is under the control of two genes, one linked to the H-2 locus of mice, the other not. Responders possessing both genes produce high anti-F titers, while the H-2-linked gene alone permits a significant but low antibody response. (Responder X nonresponder) F1 hybrids derived from parents possessing identical F molecules are nonresponders, in contrast with the domi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

1976
1976
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…I t has previously been reported that BIO.A mice, in response to low doses of C3H liver extract, are also able to produce precipitating antibodies against a non-Fantigen component of liver, but when these sera were tested against the DBA/1 serum, lines of nonidentity were seen (Silver & Lane 1979). In this study, none of the DBA/1 mice responded to multiple immunizations with C3H liver extract ( + Mice were immunized on days 0 and 28 then weekly thereafter with the liver extract in CFA.Titer taken as the reciprocal of the highest dilution of serum that bound specifically 50% of the bindable F-antigen in the radioimmunoassay described by Silver & Lane (1975). Gel1 diffusion + refers to line of identity against control anti-F serum unless nonidentity is designated.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…I t has previously been reported that BIO.A mice, in response to low doses of C3H liver extract, are also able to produce precipitating antibodies against a non-Fantigen component of liver, but when these sera were tested against the DBA/1 serum, lines of nonidentity were seen (Silver & Lane 1979). In this study, none of the DBA/1 mice responded to multiple immunizations with C3H liver extract ( + Mice were immunized on days 0 and 28 then weekly thereafter with the liver extract in CFA.Titer taken as the reciprocal of the highest dilution of serum that bound specifically 50% of the bindable F-antigen in the radioimmunoassay described by Silver & Lane (1975). Gel1 diffusion + refers to line of identity against control anti-F serum unless nonidentity is designated.…”
Section: Resultsmentioning
confidence: 72%
“…In a similar vein the question can be posed as to why only DBA/1 mice responded to this antigen when previous studies with F-antigen (Silver & Lane 1975) have involved cross immunizing a variety of inbred strains with liver extracts from every other strain without any anti-Ll being detected. The simplest explanation would be that all mice possess and are tolerant to this antigen except DBA/1 which lacks the antigen.…”
Section: Discussionmentioning
confidence: 99%
“…F antigen is a cytoplasmic water soluble liver-specific antigen which elicits an interesting immunological response in mice: thus immunization with allogeneic, but not autologous, liver leads to production of autoantibody to F antigen (anti-F-antibody). There are two isoforms of F antigen in the liver of mice (Silver & Lane 1975, Utzinger 1975 and inbred strains possessing one isoform will produce anti-F antibody in response to immunization with the other isoform from another strain, but do not respond to antigen from strains containing the same isoform (Silver & Lane 1975); however not all strains are responders to the alternate isoform. The response to F antigen is T cell dependent, and F antigen, as a hapten, may become associated with an alloantigen acting as a carrier moiety (Iverson & Lindenmann 1972).…”
mentioning
confidence: 99%
“…the F 1 immune response corresponds to that of the LR parent. 2,3 The pertinent genes were mapped to the H2A 4±6 or H2E loci, 7,8 but the role of H2 adjacent regions 9±11 and non-H2 genes 12 has also been reported.…”
Section: Introductionmentioning
confidence: 99%